RANCANG BANGUN WEBSITE MENCARI TUKANG MENGGUNAKAN FRAMEWORK LARAVEL - Mohammad Rifqi Al Hazmi (Universitas Atma Jaya Yogyakarta, 2018)
Abstract. This website was designed to address an issue of finding handyman. The idea was to make finding a good handyman easier for the users. The problem that is commonly faced in a searching process is the difficulty to find a construction worker whose skills match the needs of the existing project. It can create a fatal impact for the construction worker is one of the important factors in determining the quality of a building. Designing a website for finding handymen is then considered solve the problem since the number of internet users in Indonesia is increasing nowadays. The website is created by using Laravel framework. Laravel was chosen because it is a robust framework establishing the orderly construction that it is useful to organize the codes. The use of Laravel can also reduce the number of repetitiveness in building a complete working website. The result shows that the website to find a handyman can be built using Laravel framework. Keywords: website, Laravel, handyman, framework, PHP.Abstrak. Pada proses pencarian tukang, kendala yang sering dihadapi adalah tidak sesuainya keahlian tukang dengan kebutuhan proyek yang ada. Hal tersebut dapat berakibat fatal karena tukang merupakan salah satu faktor penting dalam menentukan kualitas sebuah bangunan. Dengan tingginya pengguna internet di Indonesia maka masalah pada proses pencarian tukang dapat dipecahkan dengan membuat website untuk mencari tukang. Website tersebut akan dibuat dengan menggunakan framework Laravel. Laravel dipilih karena merupakan framework yang kokoh dan memiliki rangka untuk membuat website yang tersusun dengan rapi, sehingga dapat membantu mengorganisir kode. Penggunaan Laravel dapat mengurangi jumlah pengulangan dalam membangun kerja situs web yang lengkap. Hasil dari penelitian ini adalah bahwa website untuk mencari tukang dapat dibangun menggunakan framework Laravel. Kata Kunci: website, Laravel, tukang, framework, PHP.